Prevalence of childhood overweight and obesity in 8 to 10 year- old students of a Municipal School In Campo Grande – Ms - Bonetto, Erick Vinicius (2012)
This paper analyses childhood obesity, taking into consideration the prevalence of overweight and obesity. Objective: to analyze the variables of weight and height in 180 schoolchildren aged 8 to 10 ( 78 girls and 102 boys) of a public school in Campo Grande – MS. Body Mass Index (BMI), according to the classification recommended by Conde and Monteiro (2006), was used to assess overweight and obesity. Literature review: The prevalence of obesity has increased significantly in the last decades, turning to be a severe issue of Public Health, especially in developed and developing countries, like Brazil. Several factors contribute directly to this“epidemics”: physical inactivity, feeding habits, genetic and endocrine diseases, among others. Materials and Methods: a tape measure and a anthropometric digital scale, with 100g accuracy have been used. Results: the prevalence of overweight and obesity accounted for 27,45% for boys, 32,05% for girls and 29,44% for the total sampling. Discussion: The number of diagnosed cases indicates a higher prevalence for girls in comparison with boys. The highest occurrence in boys and girls was at the ages of 9 (38, 10%) and 10 (35, 29%), respectively. Conclusion: the figures of overweight and obesity observed among schoolchildren in Campo Grande were significant, especially among girls.